Comparing various dose of PGE2 gel in induction of labour-maternal and fetal outcome - Menon, Maya; TA, Sridevi; Krishnamurthy, Vasantha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Induction of labour is the artificial initiation of labour before spontaneous onset of labour sets in. The frequency of induction varies by location and institution. The objective of this study was to study the maternal and fetal outcome after induction using different doses of PGE2 intracervical gel. Methods: A retrospective study done at E.S.I .C Medical College and PGIMSR, K. K. Nagar Chennai, Tamilnadu, India using data of deliveries conducted during the period November 2013 to October2014. Results: Total number of deliveries during the study period was 847, and the total numbers of cases induced were 105. Out of these patients who had undergone induction 39 received one dose, 40 received two doses and 26 received three doses in 24 hours at 6 hours interval. There was significant difference in mode of delivery (p=0.000), change in Bishop Score (p= 0.009), NICU admission (p =0.003) between the three groups. Conclusions: Our data proves that the maternal and fetal outcomes were better with one or two doses of PGE2 gel. Third dose of PGE2 gel unnecessarily prolonged the duration of labour leading to increased emergency caesarean section and increased neonatal intensive care unit admissions (NICU).